Diterminant Factors of Hemodialysis Compliance in CKD Patients in the Hospital: A Systematic Review - Edy Wiyono; Rusnoto Rusnoto; Fery Agusman Motuho Mendrofa (Indonesian Journal of Global Health Research, 2026)
hronic kidney disease (CKD) is a global health problem with increasing prevalence, particularly in end-stage patients requiring renal replacement therapy in the form of hemodialysis. The success of hemodialysis is greatly influenced by patient adherence to the treatment regimen, including dialysis attendance, fluid restriction, diet, and medication use. However, patient adherence remains variable and tends to be low, particularly with regard to diet and fluid restriction. This study aims to identify and analyze the determinant factors that influence the compliance of CKD patients in undergoing hemodialysis in hospital. This study used a systematic review with PRISMA guidelines. A literature search was conducted through electronic databases covering the period 2015–2025. Literature searches were obtained from Google Scholar, Semantic Scholar Proquest, and ScienceDirect . The keywords used were CKD, hemodialysis , determinant factors, adherence, hospital . Of the 1,145 articles obtained, 10 met the inclusion criteria and were subjected to further analysis. The results of the study showed that the dominant factors influencing patient compliance were economic factors (p = 0.009) , patient knowledge and education (p = 0.001) , and family support (p = 0.000) . In addition, the factor Occupation (p = 0.026) , duration of hemodialysis (p = 0.000) , and psychological aspects such as sleep quality (OR = 3.36 ) and depression also significantly contribute to patient compliance. These factors play a multidimensional role and interact with each other in influencing patient compliance. Adherence to hemodialysis in CKD patients is influenced by a combination of economic factors, knowledge, family support, sociodemographic factors, and psychological conditions. Interventions that emphasize financial support, increased health literacy, and active family involvement are crucial for increasing adherence, improving quality of life, and producing better clinical outcomes in hospitalized CKD patients.